The Concept Of Maqashid Sharia In The Effectiveness Of The Implementation Of Presidential Regulation No. 72 Of 2021 Concerning The Handling Of Stunting Mandailing Natal Regency - Irawan Rangkuti, Chairil; Sukiati, Sukiati; Syahmedi Siregar, Ramadhan (Dinasti Research, 2024)
This study examines the effectiveness of the implementation of Presidential Regulation (Perpres) No. 72 of 2021 concerning the handling of stunting in Mandailing Natal Regency through the Maqashid Syariah approach. Maqashid Syariah, which includes five main objectives, namely the protection of religion (Hifz al-Din), soul (Hifz al-Nafs), intellect (Hifz al-Aql), offspring (Hifz al-Nasl), and property (Hifz al-Mal), provides a holistic framework that integrates moral and spiritual aspects in public health and welfare efforts. This study aims to assess how the application of Maqashid Sharia values can strengthen the effectiveness of stunting management programs in the area. The research methodology used includes a literature study, interviews with religious leaders, government officials, and communities, field observations, and secondary data analysis. The results showed that the integration of Maqashid Syariah principles in the stunting handling program contributed significantly in several aspects: Hifz al-Din (Religious Protection): Religious education that educates about the importance of nutrition and health through schools and madrasas increases public awareness about religious responsibilities in maintaining children's health. Hifz al-Nafs (Protection of the Soul): Health programs supported by posyandu services in mosques and other places of worship facilitate community access to health check-ups and proper nutrition. Hifz al-Aql (Protection of Intellect): Providing good nutrition education to pregnant and lactating mothers and young families helps in the cognitive development of children, preventing the long-term impact of stunting on children's learning ability. Hifz al-Nasl (Protection of Offspring): Religious activities that support reproductive health and family planning help in maintaining maternal and child health, reducing the risk of stunting in the next generation. Hifz al-Mal (Protection of Property): Family economic empowerment programs integrated with stunting response efforts help increase family income, enabling them to provide nutritious food for their children. The conclusion of this study is that the application of Maqashid Sharia in the implementation of Presidential Regulation No 72 of 2021 in Mandailing Natal Regency is effective in supporting the handling of stunting. This holistic approach that combines physical, mental and spiritual aspects not only helps reduce stunting rates but also strengthens the community's social welfare and resilience. The practical implications of this research include developing an integrated education curriculum, utilizing places of worship as health centers, and empowering religious institutions and local communities in public health programs.